OBSTRUCTIVE ILEUS IN PULMONARY TUBERCULOSIS PATIENT UNDERGOING ANTI-TUBERCULOSIS THERAPY: A CASE REPORT: PULMONARY TUBERCULOSIS - Irisha Kirana Wiradisuria; Peter Ian Limas (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: One of the most serious complications arising from intestinal TB is obstructive ileus. Around 15% to 54% of gastrointestinal tuberculosis patients have concurrent pulmonary TB. Awareness of this complication matters particularly in patients already receiving anti-tuberculosis therapy. Methods: Case presentation: A 49-year-old woman with pulmonary tuberculosis, five months into treatment, presented with progressive colicky abdominal pain, distension, nausea, and obstipation. Examination showed a distended, tender abdomen with hyperactive bowel sounds. Supporting investigations revealed mild microcytic anemia, electrolyte imbalance, and radiological features of mechanical obstruction. Results: Laparotomy demonstrated multiple adhesions involving the jejunum, ileum, omentum, and mesenteric lymph nodes, with intestinal ischemia. Histopathology confirmed chronic granulomatous inflammation consistent with tuberculosis. Adhesiolysis, supportive care, and continuation of anti-tuberculosis therapy resulted in recovery. Conclusion: Intestinal tuberculosis should remain a differential diagnosis in pulmonary tuberculosis patients presenting with bowel obstruction, even during treatment. Timely surgical intervention combined with ongoing anti-tuberculosis therapy is essential to reduce morbidity.